Xen® Gel Stent versus PreserFlo™ MicroShunt as a subconjunctival shunt devices in glaucoma: a systematic review - Huda, Muhammad Khoirul; Suryono, Astrianda Nadya (Medical Journal of Indonesia, 2026)
BACKGROUND Glaucoma is the leading cause of irreversible blindness and is primarily managed by reducing intraocular pressure (IOP). Minimally invasive glaucoma surgeries, particularly subconjunctival shunt devices such as Xen® Gel Stent and PreserFlo™ MicroShunt, have emerged as alternatives to traditional trabeculectomy. This study aimed to evaluate their effectiveness in lowering IOP, reducing medication use, and assessing reinterventions and safety. METHODS A systematic review was conducted in accordance with Cochrane and PRISMA guidelines. Comprehensive literature searches were conducted across PubMed, Cochrane, EBSCOhost, and Google Scholar databases from the earliest available date to September 2023. Studies comparing Xen® Gel Stent and PreserFlo™ MicroShunt in adult patients with glaucoma were included. Data were extracted on study design, sample size, IOP outcomes, antiglaucoma medication use, reinterventions, and safety outcomes. Quality assessment was performed using the Newcastle-Ottawa Scale. RESULTS Of 5 European studies (2020–2023; 329 patients, 6–18 months of follow-up), 3 studies reported lower postoperative IOP with PreserFlo™ MicroShunt (11.8 [3.7] versus 13.6 [3.5] mmHg, p = 0.02; 10.3 [2.1] versus 14.2 [2.1] mmHg, p = 0.0005; 10.3 [3.2] versus 13.1 [6.4] mmHg, p = 0.019). Only one study noted fewer antiglaucoma medications with PreserFlo™ MicroShunt (0.2 [0.6] versus 1.1 [2.4], p = 0.04). Reinterventions including needling and bleb revisions were higher with Xen® Gel Stent (35.4% versus 11.5%; 20% versus 5%). Complication profiles varied, with hypotony more common in Xen® Gel Stent (6.5% versus 0%), hyphema more common with PreserFlo™ MicroShunt (7.7% versus 3.2%), and stent curling and migration more common with Xen® Gel Stent (15% versus 0%; 2% versus 0%), respectively. CONCLUSIONS Both Xen® Gel Stent and PreserFlo™ MicroShunt effectively lowered IOP and reduced medication burden in patients with glaucoma. PreserFlo™ MicroShunt may provide superior IOP control and fewer postoperative interventions. Further prospective studies in diverse populations are warranted.